Late Roman Spain and its cities - Kulikowski, Michael (Ancient Society and History, 2004)
Winner of an Honorable Mention in the Association of American Publishers' Professional and Scholarly Publishing Awards in Classics and Archeology The history of Spain in late antiquity offers important insights into the dissolution of the western Roman empire and the emergence of medieval Europe. Nonetheless, scholarship on Spain in this period has lagged behind that on other Roman provinces. Michael Kulikowski draws on the most recent archeological and literary evidence to integrate late antique Spain into the broader history of the Roman empire, providing a definitive narrative and analytical account of the Iberian peninsula from A.D. 300 to 600. Kulikowski begins with a concise introduction to the early history of Roman Spain, and then turns to the Diocletianic reforms of 293 and their long-term implications for Roman administration and the political ambitions of post-Roman contenders. He goes on to examine the settlement of barbarian peoples in Spain, the end of Roman rule, and the imposition of Gothic power in the fifth and sixth centuries. In parallel to this narrative account, Kulikowski offers a wide-ranging thematic history, focusing on political power, Christianity, and urbanism. Kulikowski's portrait of late Roman Spain offers some surprising conclusions. With new archeological evidence and a fresh interpretation of well-known literary sources, Kulikowski contradicts earlier assertions of a catastrophic decline of urbanism, finding that the physical and social world of the Roman city continued well into the sixth century despite the decline of Roman power. This groundbreaking study will prompt further reassessments of the other Roman provinces and of medieval Spanish history.